2015
DOI: 10.1590/1807-3107bor-2015.vol29.0075
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year analysis of the oral squamous cell carcinoma profile in patients from public health centers in Uruguay

Abstract: The aim of this study was to evaluate the demographic, clinical, and therapeutic characteristics and predictive factors of poor prognosis in patients with primary oral squamous cell carcinoma (OSCC) in Uruguay. Medical records of patients with the diagnosis of primary OSCC treated between 2000 and 2010 in Uruguayan public hospitals were selected. Data on demographic characteristics, risk factors, clinical features, treatment, and outcome were collected. Associations of independent variables with outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
31
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 20 publications
(49 reference statements)
11
31
2
6
Order By: Relevance
“…In a study conducted by Oliveira et al, there were 85.3% subjects who had habit of chewing or smoking tobacco. 22 In their study, alcohol consumption was seen in 63.5% cases. In our study, There were 18.3% (n=11) subjects having cancer of tongue.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study conducted by Oliveira et al, there were 85.3% subjects who had habit of chewing or smoking tobacco. 22 In their study, alcohol consumption was seen in 63.5% cases. In our study, There were 18.3% (n=11) subjects having cancer of tongue.…”
Section: Discussionmentioning
confidence: 86%
“…In a study conducted by Oliveira et al, the most commonly affected site was tongue (42.5%). 22 In another study conducted by Hellen-Bandeira et al tongue was the most commonly affected site followed by lower lip.…”
Section: Discussionmentioning
confidence: 90%
“…[5][6][7] Age-adjusted rates of oral cancer in India are high, i.e, 20 per 100,000 population and account for over 30% of all cancers in the country. 1,8 Tobacco use, and in particular smoking, is the largest cause of preventable death among adults in India, as it is globally.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown different patterns of oral squamous cells carcinomas in the various regions of the world, but few studies have evaluated this neoplasm in the Uruguayan population 2,9 . In addition, in Uruguay oral squamous cell carcinoma (OSCC) is diagnosed late, which provides poor prognosis and low survival rate for this disease 20 .…”
Section: Introductionmentioning
confidence: 99%